Antibacterial Effect of Aqueous and Methanolic extract of Indian bay leaves (Cinnamomum tamala) against Pseudomonas aeruginosa (The Journal of Ad-din Women's Medical College, 2023)
Objective: To investigate the antibacterial activities of Indian bay leaf extracts against Pseudomonas aeruginosa.Methods: This Experimental study was carried out during the period of July 2019 to June 2020 in the Department of Pharmacology and Therapeutics with the collaboration of Department of Microbiology, Mymensingh Medical College, Mymensingh, Bangladesh. The antibacterial activity was tested at different concentrations (20, 10, 5,2.5, 1.25 & 0.625 mg/ml) of both extracts of spice by using disc diffusion & broth dilution method. The extracts were prepared by using solvents aqueous & methanol. The test microorganisms were also tested for their activity against a standard antibiotic Gentamicin (80 mg) by broth dilution method and the result was compared with that of Aqueous and Methanolic extracts.Results: Among different concentrations of the ALE, 15mg/ml & above concentration showed inhibitory effect against Pseudomonas aeruginosa. In case of MLE, 15mg/ml & above concentration showed inhibitory effect against aforesaid bacteria. In disc diffusion method, Zone of inhibition (ZOI) in case of ALE ranged between 6-25mm at different concentration of extracts. Minimum inhibitory concentrations (MIC) of ALE were 15 mg/ml and MLE were 7.5 mg/ml against Pseudomonas aeruginosa. This result was also compared against a standard antibiotic Gentamicin where the MICs of Gentamicin were lower in comparison to MICs of ALE & MLE. The present study showed that aqueous and methanolic extracts of leaves demonstrated antibacterial effects against Pseudomonas aeruginosa.Conclusion: From the study it is clearly observed that there is definite antibacterial effect of both the aqueous and methanolic extract of leaves of Cinnamomum tamala against Pseudomonas aeruginosa. Further studies are required to detect and isolate the biologically active ingredients present in the Cinnamomum tamala which are responsible for this antibacterial effect. Hopefully, that would lead to the discovery of new and more potent antimicrobial agents isolated from Cinnamomum tamala.The Journal of Ad-din Women's Medical College; Vol. 10 (1), Jan 2022; p 4-11